"Being relieved and puzzled": A qualitative study of first time fathers' experiences postpartum in Jordan. Issue 4 (July 2020) - Al Tarawneh, Tamador; Shoqirat, Noordeen; Almalik, Mona
Abstract: Background: Although the transition to fatherhood is a point of attention for researchers, little is known about the first time father's postpartum experience. This study aims to explore the first time fathers postpartum experience in the country of Jordan. Methods: An exploratory qualitative design was used. Semi-structured interviews were conducted with a purposive sample consisting of twelve first time fathers. The study was conducted in a public university in Jordan. The data was collected in 2017 and was thematically analysed using the colour and file index method. Results: The analysis revealed two main themes. The first theme centred around a feeling of relief which can be further divided into two sub-themes of self-actualisation and continuation of the family line. The second theme centred around the feeling of puzzlement, and this can also be further divided into two sub-themes of feeling unable to deal with a newborn baby and struggling to care for a recovering wife. The study identified fathers as willing to engage in the private care of their new babies and recovering wives but at a limited level of engagement. The fathers verbalised the lack of knowledge and exhibited sociocultural stereotypes related to masculinity and the role of the man in the family. Conclusions: The first time fathers' experiences ranged from feelings of relief to puzzlement. The fathers experiences were shaped by religion, culture, and masculinity which suggests education during antepartum may enhance the experience.